Using Multiple Sources of Knowledge to Investigate Northern Environmental Change: Regional Ecological Impacts of a Storm Surge in the Outer Mackenzie Delta, N.W.T. - Kokelj, Steve V.; Lantz, Trevor C.; Solomon, Steve; Pisaric, Michael F.J.; Keith, Darren; Morse, Peter; Thienpont, Joshua R.; Smol, John P.; Esagok, Douglas (ARCTIC, 2012)
Field data, remote sensing, and Inuvialuit knowledge were synthesized to document regional ecological change in the outer Mackenzie Delta and to explore the timing, causes, and implications of this phenomenon. In September 1999, a large magnitude storm surge inundated low-lying areas of the outer Mackenzie Delta. The storm was among the most intense on record and resulted in the highest water levels ever measured at the delta front. Synthesis of scientific and Inuvialuit knowledge indicates that flooding during the 1999 storm surge increased soil salinity and caused widespread vegetation death. Vegetation cover was significantly reduced in areas affected by the surge and was inversely related to soil salinity. Change detection analysis, using remotely sensed imagery bracketing the 1999 storm event, indicates severe impacts on at least 13 200 ha of terrestrial vegetation in the outer delta. Inuvialuit knowledge identifying the 1999 surge as anomalous is corroborated by geochemical profiles of permafrost and by a recently published paleo-environmental study, which indicates that storm surge impacts of this magnitude have not previously occurred during the last millennium. Almost a decade after the 1999 storm surge event, ecological recovery has been minimal. This broad-scale vegetation change is likely to have significant implications for wildlife and must be considered in regional ecosystem planning and in the assessment and monitoring of the cumulative impacts of development. Our investigations show that Inuvialuit were aware of the 1999 storm surge and the environmental impacts several years before the scientific and regulatory communities recognized their significance. This study highlights the need for multidisciplinary and locally informed approaches to identifying and understanding Arctic environmental change. La synthèse des données d’exploitation et de télédétection de même que des connaissances des Inuvialuit a été effectuée afin de répertorier les changements écologiques enregistrés dans la région ...